CONSUMER PERCEPTIONS TOWARDS DIGITAL SHADOW ECONOMY – EVIDENCE FROM NORTH MACEDONIA - Trenevska blagoeva, Kalina; Josimovski, Sasho; Kiselichki, Martin; Pulevska ivanovska, Lidija; Mijoska belshoska, Marina (My University, 2024)
The informal economy is a global phenomenon and a threat to the entire world economy. Fueled by the rapid development of the digital economy and the increasing use of e-commerce worldwide, the informal economy is gaining momentum in the digital space as well. As volume, variety and velocity of transactions in the digital space increase rapidly, there is a growth of the number of illegal digital operators and platforms encouraging consumers’ involvement in digital shadow trade from different reasons. Undoubtedly, one of the biggest problems in the last decade is the difficulty to define and hence detect economic shadow activities, objects and entities in the digital space, which is the basis for the growth of the informal economy. Although in recent years the interest towards the forms, channels, features and scope of the digital shadow activities is increasing, there isn’t a clear understanding of digital shadow economy in the scientific literature. The variety of terms, interpretations, characteristics and aspects relevant to this phenomenon is rather wide, which determines the necessity to define the precise concept in order to detect, measure and reduce shadow activities in the digital space. Despite the prevalence of the informal exchange of goods and services in the digital space in both developing and developed countries, so far little is known about consumer attitude in this large and rapidly expanding market fueled by rapid technological advances. Hence, it is important to understand how consumers perceive the concept of digital shadow economy, are they aware of shadow economy in the digital space and how they behave online. The goal of this study is to discuss important aspects digital shadow economy and to analyze consumer perceptions towards this phenomenon in the country. It employs a quantitative research design, and a questionnaire as the instrument for data collection was distributed among more than 170 respondents. The findings provides relevant theoretical and practical implications and confirm moderate level of awareness of Gen Z towards digital shadow economy in our sample. The results also reveal some valuable insights about online consumer perceptions’ towards determinants of digital shadow consumption and what affects consumer attitude in online shopping channels. Regardless of the efforts to reduce the informal economy in the country, there is a lack of studies and empirical evidence on digital shadow economy from consumer perspective. This study contributes to the understanding of how Gen Z perceive the concept of digital shadow economy and hence can promote activities in rising awareness about the negative effects of shadow activities in the digital space, encouraging young online consumers on strong attitude in avoiding shadow channels in the digital space.
Keywords: Digital Shadow Economy, North Macedonia, Gen Z